Implementasi Gaya Kepemimpinan Situasional Kepala Sekolah Di MTsS Syarif Abbas Kabupaten Tanah Bumbu Tahun Pelajaran 2024/2025 - TRI WAHYU CHANDRA FAUZI (UNISAN JURNAL, 2025)
This study aims to examine the implementation of situational leadership styles by the principal at MTsS Syarif Abbas, Tanah Bumbu Regency, for the 2024/2025 academic year. Situational leadership is an approach that allows leaders to adapt to the needs and circumstances of their team or organization. In the educational context, this style is crucial due to the dynamic and diverse learning environment. The study employs a qualitative method with interviews and observations. Findings indicate that the principal applies a situational leadership style, where they are able to adjust their leadership approach based on the readiness level and needs of teachers and students. Data reveals that 70% of teachers feel more motivated and engaged when the principal adopts this approach. Further training is recommended to enhance the principal’s managerial knowledge in implementing this leadership style. This research provides implications for educational leadership development in Indonesia.